2016
DOI: 10.1007/s11239-016-1456-y
|View full text |Cite
|
Sign up to set email alerts
|

Early function decline after ischemic stroke can be predicted by a nomogram based on age, use of thrombolysis, RDW and NIHSS score at admission

Abstract: The availability of prediction tools for risk stratification after acute stroke is seen as a valuable perspective for tailored clinical management. This retrospective study was aimed to identify significant predictors of poor outcome in patients presenting with acute ischemic stroke, which could then be used for constructing a prediction model. The study population consisted of 837 patients admitted to the Stoke Unit of University Hospital of Verona (Italy) for acute ischemic stroke within 12 h of symptoms ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 25 publications
1
38
0
1
Order By: Relevance
“…Moreover, our study also demonstrated that NHISS on admission and age are stronger, significant and independent predictors of 3-month unfavorable outcome in ischemic stroke patients. As previously reported [2,[13][14][15][27][28][29], NIHSS score constitutes a strong independent predictor of poor outcome in patients with ischemic stroke, and age contribute to a long-term mortality and unfavorable outcome, this could be due to the fact that old age is associated with one or more cardiovascular disease such as coronary artery disease, high blood pressure, high cholesterol, atrial fibrillation, heart failure, peripheral artery disease, and cerebral amyloid angiopathy.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, our study also demonstrated that NHISS on admission and age are stronger, significant and independent predictors of 3-month unfavorable outcome in ischemic stroke patients. As previously reported [2,[13][14][15][27][28][29], NIHSS score constitutes a strong independent predictor of poor outcome in patients with ischemic stroke, and age contribute to a long-term mortality and unfavorable outcome, this could be due to the fact that old age is associated with one or more cardiovascular disease such as coronary artery disease, high blood pressure, high cholesterol, atrial fibrillation, heart failure, peripheral artery disease, and cerebral amyloid angiopathy.…”
Section: Discussionmentioning
confidence: 71%
“…To the best of our knowledge, there have only been 3 scholarly works carried out on nomograms for individualized prediction of the probability of unfavorable outcome of ischemic stroke in Caucasians (Italian) [13][14][15]. The START nomogram was designed to predict outcome after intravenous thrombolysis for stroke [14], and another nomogram model was developed in a study including 344 patients who started oral anticoagulants 1-7 days after atrial fibrillation-related stroke onset [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although no systematic studies on the correlation between these routine clinical indicators and ischemic stroke have been performed either in China or abroad, a few reports have been published that evaluated the relationship between routine blood tests and stroke. Recent reports have been published on the relationship between the neutrophil/lymphocyte ratio (Xue et al, 2017;Zhang et al, 2011), red blood cell distribution width and stroke prognosis at home and abroad (Kim et al, 2012a;Turcato et al, 2017b). In 2017, Turcato et al (2017a) found that determination of red blood cell distribution width could provide guidance on the risk of cardiovascular and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that, besides red blood cell abnormalities, many human disorders may be frequently associated with high RDW. It has been linked to ischemic cerebrovascular disease and to poorer outcome after ischemic stroke [33]. Higher values of RDW have also recently shown to be associated with increased mortality of ESRD patients [34, 35].…”
Section: Discussionmentioning
confidence: 99%